Điều khiển robot n bậc tự do - Cat, Pham Thuong (Journal of Computer Science and Cybernetics, 2018)
A hybrid control scheme is presented in this paper for the control of manipulators which have uncertainties in parameters and disturbances. The robustness is achieved by applying the  model reference Adaptive Approach in order to obtain the nonlinear compensation laws which do not require the exact knowledge of parameters and disturbances. At  first modeling of discrete control system of n  degree of freedom robot is  analysed. Then using the  second method of Lyapunov a control scheme is proposed which results in asymptotically stable system performance.